Experimental study of cyclone filters of pneumatic automatic control system of gas turbine engine for increasing degree of purification - N. V. Vologodskij; A. V. Pronevich; A. B. Yakovlev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
An experimental study of cyclone filters of various designs is conducted. The parameters that allow increasing the degree of air purification from dust are identified: air pressure at the filter inlet, working air temperature, as well as the diameter of the nozzle of the purified air consumer simulator and the diameter of the ventilation nozzle. The results obtained make it possible to increase the reliability of pneumatic units and reduce the erosive wear of their working cavities